1990
DOI: 10.1177/019394599001200507
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Expert Judgment in Content-Related Validity Evidence

Abstract: The unified conceptualization of validity with regard to content-related evidence has been expressed succinctly by the authors of the Standards for Educational and Psychological Testing (AERA et al., 1985): Content-related evidence of validity is a central concern during [instrument] development, whether such development occurs in a research setting, in a publishing house, or in the context of professional practice. Expert professional judgment should play an integral part in developing the definition of what … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
22

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(85 citation statements)
references
References 5 publications
0
63
0
22
Order By: Relevance
“…The number of items in all competence areas was increased except for the first; "organization and leadership". In line with the recommendations of Berk [22], four of the authors independently acted as experts when considering the logical consistency of the competencies and the number of items to be included in the RCS. Content and face validity were based on agreement between the four authors.…”
Section: Step 1 Construction Of the Radiographersmentioning
confidence: 99%
“…The number of items in all competence areas was increased except for the first; "organization and leadership". In line with the recommendations of Berk [22], four of the authors independently acted as experts when considering the logical consistency of the competencies and the number of items to be included in the RCS. Content and face validity were based on agreement between the four authors.…”
Section: Step 1 Construction Of the Radiographersmentioning
confidence: 99%
“…Taguchi (2006) argued that native speakers have got mastery over the situations and the communicative acts taking place. Berk (1990) argues that content-related evidence of validity is a central concern during "instrument" development and expert professional judgment should play an integral part in developing the test items and definition of what is to be measured. As expert judgment validity of the developed MCDT was proved, it can be concluded that the test enjoys a high content validity.…”
Section: Resultsmentioning
confidence: 99%
“…Secondly, findings revealed that the MDCT developed enjoyed high expert judgment validity based on content-related evidence. According to Berk (1990), content-related evidence of validity is a central concern during "instrument" development and expert professional judgment should play an integral part in developing the test items and definition of what is to be measured. The present study findings revealed a significant relationship between the rank orders of speech acts in the pragmatic test (MDCT), as the highest correlation was between apology and disagreement which was followed by the relationships between complaint and disagreement, request and refusal, request and apology, and refusal and apology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…listing symptoms, labelling anatomical diagram, making diagnostic statements). To ensure appropriateness of test content, the items and the format of the test was checked and revised by a panel of three experienced University lecturers for content validity as recommended by Berk (1990). As the test questions were unchanged for each re-assessment, the authors accept that a learning effect may well have influenced performance on subsequent re-administration of the test (immediately post-training and at one month post-training).…”
Section: Assessment Of Knowledgementioning
confidence: 99%